If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(v + 2) = 3v + -29 Reorder the terms: -4(2 + v) = 3v + -29 (2 * -4 + v * -4) = 3v + -29 (-8 + -4v) = 3v + -29 Reorder the terms: -8 + -4v = -29 + 3v Solving -8 + -4v = -29 + 3v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-3v' to each side of the equation. -8 + -4v + -3v = -29 + 3v + -3v Combine like terms: -4v + -3v = -7v -8 + -7v = -29 + 3v + -3v Combine like terms: 3v + -3v = 0 -8 + -7v = -29 + 0 -8 + -7v = -29 Add '8' to each side of the equation. -8 + 8 + -7v = -29 + 8 Combine like terms: -8 + 8 = 0 0 + -7v = -29 + 8 -7v = -29 + 8 Combine like terms: -29 + 8 = -21 -7v = -21 Divide each side by '-7'. v = 3 Simplifying v = 3
| 3z+4x-5=0 | | .5(x-2.3)=1.8 | | 2+x-3+x=9+x | | x^4+x-50=0 | | 10(t-5)+4t=7(2t+3)-10 | | 3x+9=2(x+7) | | x+6*2=x-13 | | t+2t-19=0 | | -3(-x)+3x=24 | | 3(a-2)=10 | | 3k-8=-3k+10 | | 2y+2y-8+3y=9 | | 5x-5=4x+9 | | 0=6y+6 | | RT=2x+4 | | 3x+5x-5=11 | | 8-2p=p+3 | | (5x-2)(3x+2)=0 | | a-9a+18=0 | | 15=-3(m+5) | | x^4+3x^3-3x^2-11x-6=0 | | 3x+4x-9=19 | | 3x+5=0.2(15x+10) | | p=s+6 | | 0.25+0.10(x+85)=15.25 | | y=15x-30 | | 0.25x+0.5(x+6)=3.90 | | 2(p-4)=10 | | 3x-5(x-4)=-6+3x+1 | | -20=4x+8 | | 81-6= | | -54x^3+24x=0 |